Low-intensity ultrasound lysis of amyloid microclots in a lab-on-chip model - Rasouli, Reza; Hartl, Brad; Konecky, Soren D. (Frontiers in Bioengineering and Biotechnology, 2025)
Amyloid fibrin(ogen) microclots are misfolded protein aggregates with β-sheet structures that have been associated with Long COVID and numerous thrombo-inflammatory diseases. These microclots persist in circulation and obstruct microvasculature, impair oxygen transport and promote chronic inflammation. Conventional thrombolytic therapies such as recombinant tissue plasminogen activator (rtPA) show limited efficacy against these microclots due to their structure and composition. In this study, we assess the impact of low intensity focused ultrasound (LIFU) stimulation on amyloid microclot fragmentation, the role of cavitation in this process and investigate whether microbubble-assisted ultrasound can enhance their lysis. Amyloid microclot models were generated using freeze-thaw cycles followed by incubation. Microclots were exposed to ultrasound waves at 150, 300, 500 kHz, and 1 MHz under four conditions: ultrasound alone (US), ultrasound with microbubbles (MB + US), ultrasound with rtPA (rtPA + US), and ultrasound with both microbubbles and rtPA (MB + rtPA + US). Low-frequency ultrasound at 150 kHz resulted in a significant clot lysis with up to three-fold reduction in both clot size and the number of large clots. The addition of microbubbles enhanced clot lysis at 150, 300, and 500 kHz. These findings suggest that ultrasound, particularly at 150 kHz is a promising method for amyloid microclot lysis. The combination of ultrasound with microbubbles and rtPA further improved clot fragmentation, rendering it a potential therapeutic tool for conditions like Long COVID.